The degree of employment of distance education among secondary teachers from the point of view of school principals in Palestine in light of the Corona pandemic - Droubi, Aseel Fuad; Al-Sayegh, Ashraf Munther (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the degree of employment of distance education among secondary teachers from the point of view of school principals in Palestine in light of the Corona pandemic. (230) and the percentage equals (43%), distributed among all secondary schools in the districts of (Nablus, Jenin and Tulkarm). The results of the study indicated that the employment of distance education among teachers of Palestinian secondary schools was medium, where the arithmetic mean was (3.13), and the results also showed that there are no statistically significant differences between the average responses of the study sample towards the degree of employment of distance education among teachers due to the variables (sex, educational qualification), while there are statistically significant differences due to the variable (years of experience), where the highest arithmetic averages were in favor of a level of 5-10 years, and the lowest for a level of less than 5 years. In light of these results, it is recommended to work on training teachers to increase their ability to employ distance education, and to make e-learning a teaching style for some courses even in the event of the disappearance of the Corona pandemic.